Adulting made easy : things someone should have told you about getting your grown-up act together - Morin, Amanda (Get Creative 6, 2021)
"In the age of COVID and chaos, social media and sky-high rents, adulting can be hard. But it doesn't have to be! This book answers questions young adults sometimes don't even know to ask. Chapters are ordered in a way that puts at the forefront what young people are thinking about now, with a new generation going into adulthood more likely to be living with family; politically and civically engaged; and using social media as a communication tool or platform. Includes money, jobs, communication, social media, identity, health insurance, living situations, housework, travel and troubleshooting"--